Status and Pattern of Financing the Public Libraries in Kerala - Sudha, A. (Journal of Information and Knowledge, 2012)
Adequate levels of funding are crucial to the success of a public library to fulfill its objectives. This study traces the various sources of finance of the Kerala State Library Council. The State government‟s contribution and cess collected as per the provision in the Act are the primary sources of revenue of the public libraries in Kerala.It depicts the total revenue and per - capita revenue of the Council over a period of ten years from 2001 to 2011. It also depicts the total expenditure, annual grant to the affiliated public libraries, and per-capita expenditure of the Council for the users. The expenditure of the Council towards various services of the public libraries is presented in this study. This study makes an attempt to discuss the important critical issues in the public library finance and conclude that it is the duty of the government to give due importance for the development of the public libraries with the provision of more funds.